OPTIMIZATION OF DNA EXTRACTION FROM FILAMENTOUS FUNGI ALTERNARIA SP. AND FUSARIUM SP. - Turzhanova , A.S.; Rukavitsyna , I.V.; Khapilna , O.N.; Kalendar , R.N. (Eurasian Journal of Applied Biotechnology, 2018)
Filamentous fungi have strong cell walls which are lysis resistant and contain high levels of proteins, polysaccharides, and other secondary metabolites. Accurate identification of fungal pathogens using a sequence-based approach required an extraction method that yielded template DNA pure enough for polymerase chain reactions (PCR) or other types of amplification. Therefore, the objective of this study was to develop and standardise a rapid, inexpensive DNA extraction protocol applicable to major fungal phyla, which would yield sufficient template DNA pure enough for PCR and sequencing. In this research, phytopathogenic Alternaria and Fusarium fungi from contaminated wheat seeds were used. Four methods were tested for genomic DNA isolation: CTAB, an SDS method with modification, the Benjamin Schwessinger method and a Qiagen DNeasy Plant Mini Kit. High qualitative and quantitative characteristics were obtained from the DNeasy Plant Mini Kit and the acid CTAB-buffer (рН ≤ 5). The QIAGEN plant DNeasy and CTAB methods may be applicable to other fungi and effectively implemented in other laboratories.